A Comparison Study Of Red Blood Cell Indices In Southeast Asian Ovalocytosis (Sao), Iron Deficiency Anaemia (Ida) And Sao With Concomitant Ida - Ghazali, Nik Shaida Shamim Nik (2019)
Introduction: Southeast Asian ovalocytosis (SAO) and iron deficiency anaemia (IDA) are common in Malaysia. Both have specific red blood cells (RBC) parameters pattern but overlapping morphological features. When SAO patients having concomitant IDA, it is quite challenging to differentiate them. Thus, the study aims to study RBC parameters in three groups of individuals with SAO alone, IDA alone and SAO with concomitant IDA and identifying potential parameters in discriminating them. Methodology: A retrospective cross-sectional study was conducted among 79 subjects from Institut Perubatan dan Pergigian (IPPT), USM (30 cases with SAO alone and IDA alone and 19 cases SAO with IDA). The data were obtained from the laboratory information system (LIS) of Advanced Diagnostic Laboratory from January 2010 to May 2019. Univariable analysis (One-way ANOVA or Kruskal-Wallis test) was used to compare the red blood cell parameters between the three groups, which include RBC, Hb, MCV, MCH, MCHC and RDW. Statistical significance was set at a P-value of <0.05. Results: SAO with concomitant IDA showed mean of RBC, Hb, MCV, MCH, MCHC and RDW of 3.5 x 106/μL, 9.2 g/dL, 74.6 fL, 25.7 pg, 33.7 g/dL and 46.0 fL, respectively. It was found that the Hb, MCV and MCH of SAO with concomitant IDA group were lower compared to the SAO alone group with significance P-value (P<0.001). However, the RBC count, MCHC and RDW parameters were not significant between both groups (P>0.05).